2019
DOI: 10.3390/w11102143
|View full text |Cite
|
Sign up to set email alerts
|

A Spatiotemporal Analysis of Nitrogen Pollution in a Coastal Region with Mangroves of the Southern Gulf of Mexico

Abstract: Nitrogen pollution is a growing problem in many rivers and estuaries of the Southern Gulf of Mexico. In Costa Esmeralda, a tourist destination in Veracruz, the increasing nitrogen pollution is causing severe environmental damage. However, very few studies addressed nitrogen pollution and its consequences for beaches and mangroves. In this study, a spatiotemporal evaluation of nitrogen concentrations was performed along two rivers discharging into Costa Esmeralda and the associated mangrove and coastal areas. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
1
9
0
1
Order By: Relevance
“…All monitoring sites were placed in the same class by the GNMP and the GLUP indexes, indicating that land use pressures were detected accurately. The results indicate that Nautla and Tuxpan estuaries have the highest urgency for N pollution management which agrees with previous studies which indicated the existence of N pollution in these estuaries (González-Marín et al, 2017;Marín-Muñiz et al, 2016;Rivera-Guzmán et al, 2014;Rodríguez-Romero et al, 2018;Temino-Boes et al, 2019). Studies in Nautla river indicated that human settlements are a major source of N pollution to the river at its lower course (Rodríguez- Romero et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…All monitoring sites were placed in the same class by the GNMP and the GLUP indexes, indicating that land use pressures were detected accurately. The results indicate that Nautla and Tuxpan estuaries have the highest urgency for N pollution management which agrees with previous studies which indicated the existence of N pollution in these estuaries (González-Marín et al, 2017;Marín-Muñiz et al, 2016;Rivera-Guzmán et al, 2014;Rodríguez-Romero et al, 2018;Temino-Boes et al, 2019). Studies in Nautla river indicated that human settlements are a major source of N pollution to the river at its lower course (Rodríguez- Romero et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…The aim of our approach is to evaluate the pollution within the estuary to estimate the potential consequences of nitrogen pollution to the surrounding ecosystems such as beaches or mangroves. For example, the consequences of nitrogen pollution in Nautla estuary include the degradation of touristic beaches with consequences for the local economy, as well as the deterioration of mangroves (Temino-Boes et al, 2019). But the impact of high nitrogen concentrations in Papaloapan river in the eutrophication of the Gulf of Mexico as a whole would be much worse than N pollution in Actopan river.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations